Servant Leadership and Followers Prosocial Rule-Breaking: The Mediating Role of Public Service Motivation - Khan, Naqib Ullah; Zada, Muhammad; Ullah, Asad; Khattak, Afraseyab; Han, Heesup; Ariza-Montes, Antonio; Araya-Castilo, Luis (Frontiers in Psychology, 2022)
This research explores the effect of servant leadership on prosocial rule-breaking (PSRB) and the mediating mechanism of public service motivation (PSM) between the association of servant leadership and PSRB. The said phenomenon is examined in the civil service context of Pakistan during the continuing crises of the COVID-19 pandemic, a situation where the traditional civil service policy and rule system has become highly complicated for passionate employees’ service performance and efficiency, and where servant leadership has received greater attention for inspiring the attitudinal and behavioral outcomes of frontline workers during the pandemic. Data were collected from 546 frontline workers of the corona relief tiger force. The findings of the study revealed that servant leadership has a significant effect on PSRB and PSM, and that PSM significantly promotes PSRB. The results also revealed that servant leadership has a significant impact on PSRB via engendering PSM.